Implementasi Perangkat IoT Terdistribusi untuk Pengendalian dan Pemantauan Irigasi Air Menggunakan Metode Drip dan Penyemprotan Nutrisi dalam Sistem Pertanian Cerdas - Sinambela, Eka Stephani; Panjaitan, Jessica; Pakpahan, F. Salmonso; Simamora, Jenris; Simatupang, Frengki; Wowiling, Gerry Italiano; Sigiro, Marojahan Mula Timbul; Manalu, Istas Pratomo; Silalahi, Sari Muthia; Siagian, Pandapotan (Journal of Information System Research (JOSH), 2025)
Internet of Things (IoT) technology can enhance agricultural productivity through automated monitoring and control systems. However, many existing IoT systems are still centralized and inflexible, making integration with other systems in the field challenging. This research develops a distributed and modular (plugin) automated monitoring and control system for soil moisture management, specifically for potato cultivation. The system utilizes soil moisture sensors to measure moisture levels, which are processed by an ESP8266 microcontroller. The data is used to automatically control irrigation flow, maintaining soil moisture within the optimal range for potato plants. Additionally, the system includes a backup feature that allows manual operation in case of automatic system failure. Field tests demonstrate that the system effectively maintains soil moisture at optimal levels. Its manual operation feature also ensures continued functionality during disruptions. Therefore, this system is expected to improve efficiency and resilience in agricultural land management, particularly in dynamic environmental conditions.